Highly efficient synthesis and characterization of the GPR30-selective agonist G-1 and related tetrahydroquinoline analogs - Burai, Ritwik (2010)
[Image: see text] The GPR30 agonist probe G-1 and structural analogs were efficiently synthesized using multicomponent or stepwise Sc(III)-catalyzed aza-Diels Alder cyclization. Optimization of solvent and reaction temperature provided enhanced endo-diastereoselectivity.